Unpublished folk dances of libon: basis for educational resource guide in folk dancing - Dela Torre, Jhodie Braga (San Miguel, Iriga City: University of Saint Anthony, 2018)
Unpublished folk dances of libon: basis for educational resource guide in folk dancing.
Includes bibliographical references.
English
Keywords: Educational resource guide